Enhancing Local Government Revenue in Vietnam - Quang Phat, Bui (VNU JOURNAL OF ECONOMICS AND BUSINESS; Vol 37 No 1, 2021)
The paper analyzes the current status of local government revenues in Vietnam base on two indicator groups: The size and The structure of local government revenues. In addition, the paper also compares the revenue among local governments, analyzes the causes that led to the differences. Some recommendations are proposed to enhance local government revenues in Vietnam. This is an important basis to promote local government revenues through decentralized revenues and at the same time reduce the burden for central government.